Binyat an-Na't wa al-Man'ut fi Shi'r Ahmad Shawqi: Dirasah Halah fi Qasidat "Dhikra al-Mawlid" - Ahfa Rahman Syah; Juwika Afrita (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
The adjective and its described noun (na’t and man’ut) are fundamental elements of Arabic grammar. In the context of poetry, their function is not limited to clarifying meaning but extends to beautifying language, adding balance, and highlighting the aesthetic dimensions of the text. In the works of Ahmad Shawqi especially poem Dzikra al-Maulid, the use of na’t and man’ut appears creatively to express profound emotions and convey complex meanings. This study aims to analyze the structure of na’t and man’ut in the poem Dzikra al-Maulid while exploring how this linguistic structure is employed to enhance the religious and literary meanings that distinguish the poem. Additionally, the study seeks a deeper understanding of the grammatical tools Ahmad Shawqi used to achieve harmony between form and content. The study employed qualitative methodology, with descriptive analysis technique with the poem Dzikra al-Maulid, as the primary source. The analysis results indicate that adjectives are widely used to clarify nouns and convey deeper poetic meaning. Examples from the analysis reveal the role of adjectives in providing additional detail that enhances poetic imagery and clarifies meaning. For instance, the word "ghadaah" functions as an adjective that specifies the timing of an action, adding vibrancy to the poetic scene. The word "al-jamaal" highlights the association of description with beauty, creating emotional tension. Similarly, "yawman" serves as a temporal adjective, and "bayna al-dhuloo’" as a locational adjective, both strengthening the precise depiction of state and place. Adjectives such as "min hadeed" emphasize strength and steadfastness rather than emotional vulnerability. This demonstrates that adjectives enrich poetic imagery and enhance emotional and intellectual expression, making the meaning of the poem deeper and more impactful